Pengendali Saklar Listrik Melalui Ponsel Pintar Android - Vidy Masinambow; Meicsy E.I Najoan; Arie S.M. Lumenta (Universitas Sam Ratulangi, 2014)
Abstractâ€”With the development of technology such as smart phones that are already widely owned as well as the development of network technology can be used to overcome the problem of electricity consumtion. Electrical switches can be replaced by using the equipment controlled through a relay and network-based mikrokontler equipment so that it can connect to the smart phones which is mounted control program will be used to resolve the issue.Presence wifi shield equipment that can communicate with the microcontroller through serial communication so that information in the form of commands on / off switch that is sent from a smart phone with wireless connection to the equipment shield is a choice of solutions to address the replacement power switch.From the experimental results with the use of such technology, the Android-based smart phones that installed the control program can turn off the power switch or turn on electrical appliances from a considerable distance (as far as wifi connection is available). Â Keywords: Android Smartphone, Electrical Switches,Microcontroller, Relays,Â Wifi Shield Abstrak- Dengan perkembangan teknologi seperti ponsel pintar yang sudah banyak dimiliki orang serta perkembangan teknologi jaringan dapat digunakan untuk mengatasi masalah penghemataan listrik. Saklar listrik dapat diganti dengan menggunakan peralatan relay dan dikendalikan melalui peralatan mikrokontroler berbasis jaringan sehingga dapat terhubung ke ponsel pintar yang sudah terpasang program pengendali akan digunakan untuk mengatasi masalah tersebut. Adanya peralatan WifiShield yang dapat berkomunikasi dengan mikrokontroler melalui komunikasi serial sehingga informasi berupa perintah on/off saklar yang dikirim dari ponsel pintar dengan koneksi wirelesske peralatan wifishieldmerupakan pilihan solusi untuk mengatasi pengganti saklar listrik. Dari hasil percobaan denganmenggunakan teknologi tersebut, ponsel pinter berbasis androidyang terpasang program pengendali saklar listrik dapat mematikan atau menghidupkan peralatan listrik dari jarak yang cukup jauh (sejauh koneksi wifi yang tersedia). Kata kunci: Mikrokontroler, Ponsel Pintar Android,Relay, Saklar Listrik, WifiShield.